2021
DOI: 10.1155/2021/3634548
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire Survey-Based Quantitative Assessment of the Impact of Transitional Care on Self-Management of Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease

Abstract: Background and Objective. Chronic obstructive pulmonary disease (COPD) features high morbidity. Different nursing interventions can relieve patient’s burden. This investigation quantitatively assessed the impact of transitional care (TC) on self-management of patients with acute exacerbation of COPD based on a questionnaire survey. Methods. Clinical information of 78 COPD patients treated with TC (intervention group) or routine care (control group) in Shanghai Pulmonary Hospital during March 2019 and August 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 29 publications
0
4
0
8
Order By: Relevance
“…Da avaliação efetuada, releva o facto da qualidade metodológica geral dos estudos ser relativamente alta, com pontuações superiores a 9 para a revisão sistemática e para os estudos randomizados. Nos estudos randomizados (13,14,15) , as inconformidades relacionaram-se com a falta de evidência de procedimentos de cegagem dos avaliadores e/ou dos participantes e com o facto de não haver referência acerca dos avaliadores dos resultados. Importa referir que para a avaliação da qualidade metodológica do estudo de Kargiannakis et al (14) , houve necessidade de identificar fontes de informação adicionais, nomeadamente o protocolo do estudo piloto para o ensaio clínico randomizado (16) , conforme sugerido pelos autores.…”
Section: Figura 1 -Diagrama De Seleção Dos Artigos (Adaptado De Prism...unclassified
See 2 more Smart Citations
“…Da avaliação efetuada, releva o facto da qualidade metodológica geral dos estudos ser relativamente alta, com pontuações superiores a 9 para a revisão sistemática e para os estudos randomizados. Nos estudos randomizados (13,14,15) , as inconformidades relacionaram-se com a falta de evidência de procedimentos de cegagem dos avaliadores e/ou dos participantes e com o facto de não haver referência acerca dos avaliadores dos resultados. Importa referir que para a avaliação da qualidade metodológica do estudo de Kargiannakis et al (14) , houve necessidade de identificar fontes de informação adicionais, nomeadamente o protocolo do estudo piloto para o ensaio clínico randomizado (16) , conforme sugerido pelos autores.…”
Section: Figura 1 -Diagrama De Seleção Dos Artigos (Adaptado De Prism...unclassified
“…Effect of a Health Belief Model-based nursing intervention on Chinese patients with moderate to severe chronic obstructive pulmonary disease: a randomized controlled trial (13) 10/13 1c E5. Questionnaire Survey-Based Quantitative Assessment of the Impact of Transitional Care on Self-Management of Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease (15) 9/13 1c VOL. 7, Nº 1…”
Section: E3 Does Telehealth Monitoring Identify Exacerbations Of Chro...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that, by providing TCS to COPD patients, their readmission and hospitalization periods decrease [9], and their dyspnea [9], quality of life [10], and depression scores [11] improved. Specifically, in the study by Ko et al [9], a respiratory nurse provided two hours of education on drug use, smoking cessation, and respiratory management to patients discharged from the hospital owing to exacerbation of COPD while a physical therapist performed pulmonary rehabilitation.…”
Section: Introductionmentioning
confidence: 97%
“…Consequently, the hospitalization period due to readmission, acute exacerbation, and the degree of dyspnea were reduced in the intervention group (IG). Similarly, in Xu's study [10], patients with COPD who were admitted to the hospital because of acute exacerbation were provided self-management education. After discharge, health guidance was provided via phone or messaging.…”
Section: Introductionmentioning
confidence: 99%